Estimation and linkage between behavioral problems and social emotional competence among Pakistani young school children. - Arooj Najmussaqib; Asia Mushtaq (PLoS ONE, 2023)
Behavioral problems are commonly occurring concerns in school children and if left unidentified can result in worse outcomes in any society. The research aims to explore the prevalence of behavioral problems and its association with social emotional competence in young school children from a community sample of Islamabad, Pakistan. The cross-sectional study was conducted from April to June 2021 in four public primary schools in Islamabad, Pakistan. Two stage cluster sampling was used to select study sites. The sample comprised 426 school children (males = 182, females = 195) aged 4-8 years (Mean age = 6.5, SD = 1.09), from three different grades kindergarten, 1, and 2, respectively. The Child Behavior Checklist (CBCL) and Social Emotional Development Assessment (SEDA) were used to screen behavioral problems and social emotional competences of children. Data were analyzed using Stata 17. Prevalence for overall behavioral problems accounted for 65.4% (4-6 years) and 36.2% (6-8 years) in the abnormal (borderline and clinical) ranges of total problems. Social emotional competence scores were found significantly negatively associated with behavioral problems of children. The high prevalence necessitates the provision of mental health care to school-aged children. The findings should be taken as a call to Pakistan's policymakers, clinicians, and researchers to develop proper screening and management protocols for early intervention.